Gods, or Mortals? Erroneous Identifications of Certain Sculptures - Carrasco Ferrer, Marta; Elvira Barba, Miguel Ángel (Eikón / Imago, 2017)
As in many museums that contain ancient works of art, in the Prado museum there are many sculptures that have been misleading and imaginary over the centuries. We emphasize some of them and we focus so much on those that have received the name of Antinous and in which representing the own Antinous have been copnocidas with other names.